Investigation of stability for composite operational amplifiers - Schneider, Carl (Department of Electrical Engineering, 2023)
In the study of a paper by Campbell and Stephenson [1] on the possibilities of employing composite operational amplifiers to extend the high frequency performance of conventional RC active filters · it became evident that theoretical predictions of stability and experimental results did not agree. Other publications concerned with composite operational amplifiers merely presented circuits where it was implied that these would work under most conditions. However, when one set out to build such amplifiers and investigated their behaviour in frequency filters it emerged that severe stability problems beset such studies. The work here presented was initiated by the fact that hitherto the problem of stability had not received the attention that it warranted. Experimental results obtained by Campbell and . Stephenson made use of the Composite Two Operational Amplifier ( C20A ) by Mikhael and Nessim [2]. It was for this reason that investigations presented here also made use of this amplifier Theoretical studies by Campbell and Stephenson showed significant deviations from the experimental results, something which obviously required further investigation. By using the Nyquist Diagram Stability analysis technique to determine the stability of the open loop system it became possible to investigate the effect of the higher order terms of operational amplifier models. In fact, using Millman's [37] single, double, and triple pole models of the operational amplifier the results obtained came close to those obtained by the experiments. However. the procedure involves lengthy mathematical manipulations, and it was therefore decided to apply a standard stability evaluation technique of sufficient accuracy. The relatively simple Routh Criterion Stability analysis technique was considered where stability could be very conveniently established.